Unmanned aerial vehicles for Internet of Things (IoT) : concepts, techniques, and applications - Mohindru, Vandana; Singh, Yashwant; Bhatt, Ravindara; Gupta, Anuj Kumar (John Wiley & Sons, Inc. ; Scrivener Publishing, 2021)
"The 15 chapters in this book explore the theoretical as well as a number of technical research outcomes on all aspects of UAVs. UAVs has widely differing applications such as disaster management, structural inspection, goods delivery, transportation, localization, mapping, pollution and radiation monitoring, search and rescue, farming, etc. The advantages of using UAVs are countless and have led the way for the full integration of UAVs, as intelligent objects into the IoT system. The book covers such subjects as: efficient energy management systems in UAV based IoT networks, IoE enabled UAVs, mind-controlled UAV using Brain-Computer Interface (BCI), the importance of AI in realizing autonomous and intelligent flying IoT, blockchain-based solutions for various security issues in UAV-enabled IoT, the challenges and threats of UAVs such as hijacking, privacy, cyber-security, and physical safety"--